PRADIGMA ISLAM NUSANTARA DALAM AL-QUR’AN - Rizqiyah Rizqiyah; Khoirit Tamam; Ikhwan Marzuqi (Universitas Al-Amien Prenduan, 2026)
The paradigm of Islam Nusantara refers to a way of understanding Islamic teachings that emphasizes the balance between the universal values of Islam and the socio-cultural context of Indonesian society. In this view, Islam is not only regarded as a normative theological system but also as a cultural force that dynamically engages and adapts to local traditions. From the perspective of the Qur’an, the paradigm of Islam Nusantara finds its theological foundation in verses that emphasize the importance of ‘urf (local wisdom) dan tawassuṭ (moderation). These Qur’anic principles guide Muslims to embody a form of religiosity that is compassionate, moderate, and respectful of diversity. Through this approach, Islam in the Indonesian archipelago does not lose the purity of its creed but rather enriches its expression through local culture and positive traditions. This paradigm also serves as an alternative to transnational Islamic movements that often lean toward textualism and exclusivity. Thus, from the perspective of the Qur’an, Islam Nusantara can be understood as a manifestation of Islam’s principle of rahmatan lil ‘alamin, promoting peace and harmony amid human diversity.